the area of the triangle formed by the tangent at the pt. (a,b) to the circle x2 +y2 =r2and the coordinate axis


 

2 years ago

Share

Answers : (1)

                                        

Equation of tangent is 


 


ax+by-r^2 = 0


In x-y intercept form


 


x/(r^2/a) + y/(r^2/b) = 1


 


x-intercept = r^2/b


y-intercept = r^2/b


 


Area of triangle = 1/2*r^2/b*r^2/b = r4/(2ab)

2 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
find the angle between the two st lines 3x=4y+7 and 5y=12x+6 and also the equations to the two lines which pass through the point (4,5) and make equal angles with the two given lines
 
 
Ans: Hello student, Please find answer to your question below …...........(1) ............(2) Angle b/w two lines: Let the slope of the lines be ‘m’ which make equal angle...
  img
Jitender Singh one month ago
find eqn. of a line passing through intersectin of lines x+y+1=0 and 2x-3y-1=0 and passing through (1,1) whose slope is 2 units
 
 
this question is to be done by done by the method of family of lines. so,by this method-(x+y+1)+lambda(2x-3y-1)=0 now x=--2/5 and y=--3/5 are the solutions of the equation x+y+1 =0 and...
 
vineet chatterjee one month ago
Integrate cosecx.sec3x
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar one month ago
If A+B=π/3 and cosA+cosB=1 then which of the following is true? cos(A-B)=1/√3 |cosA-cosB|=√(2/3) cos(A-B)=-1/3 |cosA-cosB|=1/2√3
 
 
Hello student, please check the solution of your question. Given below: cosA+cosB=1 2cos(A+B/2)cos(A-B/2)=1 2(root3/2)cos(A-B/2)=1 cos(A-B/2)=1/root3 cos(A-B)=2cos 2 (A-B/2)-1= 2*1/3-1= -1/3...
  img
Sunil Raikwar 11 days ago
 
Sir option 2 is also a answer. How?
 
Abhigyan 3 days ago
see attachment and explain it
 
 
Hello student, operating R1=R1-R2-R3 we get L.H.S= By taking 2 commonout of R1 and then operating R2=R2+R1 and R3=R3+R1 we get =2[c 2 (a 2 b 2 -0)-b 2 (0-a 2 c 2 )] =4a 2 b 2 c 2
  img
SHAIK AASIF AHAMED one month ago
View all Questions »